Exploring the Communication Forms of 4-6 Years Old Children at Rumah Pelangi Sant Egidio - Dewi, Ni Putu Della Prasanthi; Malini, Ni Luh Nyoman Seri; Arka, I Wayan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study explores how 4-6-year-old children at Rumah Pelangi Sant Egidio use verbal, nonverbal, and multimodal communication to express themselves and engage with their environment. Using qualitative methods like observation and interviews, the research applies Fleming's VARK model and Bruner's theories on active learning. At Rumah Pelangi Sant Egidio, communication includes verbal language, gestures, and body language, each enhancing understanding and interaction. Visual aids, storytelling, and multimodal approaches, integrating various sensory channels, are crucial for young learners. These methods foster language development, social skills, and cognitive growth. Children naturally use diverse communication styles, including activities like puzzle-solving and interactive technology, to develop teamwork, critical thinking, and creativity. By integrating these communication forms, educators can create effective and inclusive learning environments.